Boosting the Zn-ion transfer kinetics to stabilize the Zn metal interface for high-performance rechargeable Zn-ion batteries. Issue 31 (27th July 2021) - Hong, Lin; Wu, Xiuming; Ma, Chao; Huang, Wei; Zhou, Yongfeng; Wang, Kai-Xue; Chen, Jie-Sheng
Abstract : An artificial SEI film based on Zn-intercalated montmorillonite was designed to tune the deposition behaviour of Zn 2+ ions on the surface of Zn anode. Abstract : Metallic zinc is widely considered as the most promising anode candidate for next-generation rechargeable aqueous batteries owing to its high volumetric capacity and intrinsic safety. However, the inferior reversibility caused by uncontrolled dendrite growth and parasitic side reactions severely impedes the commercial application of rechargeable Zn-based batteries. Herein, a fast Zn-ion conductor, Zn-intercalated montmorillonite (Zn-Mont), is designed as an artificial solid/electrolyte interphase (SEI) film to tune the transfer and deposition behavior of Zn 2+ ions on the surface of Zn anodes. Benefiting from the low Zn-ion migration energy barrier and Zn ion-selective pathway, the Zn-Mont coating could guarantee a homogeneous Zn-ion flux, and fast Zn 2+ transfer kinetics, and avoid the ion/electron accumulation at the interface of the anode, thereby suppressing the growth of Zn dendrites. In addition, the Zn-Mont layer can prevent direct contact of the Zn metal with bulk electrolyte, alleviating the water/O2 -induced side reactions. Consequently, high reversibility (coulombic efficiency > 99.6%), long-time stability (over 1000 cycles), and ultralow polarization (overpotential ≈ 28 mV) are achieved. When coupled with the MnO2 cathode, Zn@Zn-Mont||MnO2 full cells deliver outstanding cycling stability with 85.4% capacity retention (calculated based on the specific capacity of the 5th cycle) after 1000 cycles at 2C.